An application of a decomposed ortho-diagonal method to discrete polyoptimization of a hall with spatial grid structure - Paczkowski, Witold M.; Jendo, Stefan (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with application of the ortho-diagonal (O-D) method of finding the non dominated sets of solutions and evaluations for discrete polyoptimization problems. First, the (O-D) method was modified for finding minimum of a scalar function. The mono tonicity property of a vector objective function is used by the (O-D) method for consecutive finding of jth-criteria partial non dominated sets, j € {1, 2, ... ,J}. To find the nondominated evaluations sets the discrete neighbourhoods S of the point Xi are investigated starting from the solution xi which minimizes the first objective function. In this way the consecutive non dominated solutions XkND are determined. An accuracy of solution and CPU computing time depend on the way the discrete neighbourhoods S of the point xi in the design space are defined. The algorithm of the (O-D) method is applied to solve the discrete polyoptimization of a hall with spatial grid structure.